Resistência à maquiagem: práticas cotidianas e não consumo - Eliane Braganca de Matos (2013)
The purpose of this work is related to the identification of a structure that combines both the antecedents of resistance, as a lbrm ofexccution, motivation and symbolic negotiation, The idcntiiication of an articulate resistance structure will allow to verify how the symbolic circulation through consumption environments is established, given that it is understood that both consumption and resistance relations are interactive and recursive. Based on a broad review of studies related to anti-consumption and consumer resistance and resistance, this thesis used a qualitative methodology through the Extended Case Method (EMC) developed by Burawoy (1998), which deals with the detailed analysis of narratives of consumption, eontextualized in stories life of the respondents. Chosen were 4 cases ofwomen who do not wear makeup. The product category was chosen because of the interest of investigating thc importance of the context of resistance to consumption in a market with a large sales volume and a very representative symbolic meaning in the cu1tu1·e o1` consumption of the female public. Furthermore, wc sought to investigate individualized and everyday consumption resistance behaviors, which are not inserted in the context of organized and collective movements. The analysis of research data indicates that resistance to the use of makeup has the habitus (Bourdieu, 1997) as a strong antecedent and trainer behavior and personal identity (Foucault, 2001 and Taylor, 1997) as a central guiding project. These two constitutional and sustenance resistance vectors lead to a re-signitication ofthe beauty capital and the products or artilacts related to its construction (Hogg, 1998). The importance of identity as basic guidance vector of resistance allows approximations between the concept or typology of project resistance (Cherrier, 1998), and the "t" uti1e" resistance identitied by Ritson and Dobsha (1999) and with Holts reflexive resistance (2002). lt was also possible to identify, through the interviews, that the navigation between consumption environments (Ligas and Cotte, 1999; Hogg and Michel, 1996; Hogg, 1998; Bannister and Hogg; 2003 and Hogg et al., 2009) is guided by this identity project, which interacts with the symbolic constructions of trademarks and products, strengthening, as in the case of this study (or weakening, hypothetically) the behavior of resistance and the identity project itself Given that resistance is a resulting part of the personal identity project, it comes into effect in practice through the consumption of substitute products, chosen and combined inside a floating logic, which is mutable and individualized. These everyday practices based on an alternative signification system explicit Certeaus conceptualization (1990) of resistance as tactic and consumer action, which unexplainably and anonymously subverts the discursive logic, contesting the position and authority of the market (Penaloza and Price, l993).This research sought to contribute to the broadening and consolidation ofthe knowledge basis of incipient theory of consumption resistance, suggesting a research agenda on other product categories that have not been investigated in the literature.